PENERAPAN ALGORITMA NAIVE BAYES PADA APLIKASI PENELUSURAN ALUMNI (TRACER STUDY) BAGI TAMATAN SMKN 2 KOTA BENGKULU - susanto, teguh; Muntahanah, Muntahanah (Universitas PGRI Semarang, 2022)
Alumni are a very valuable asset for an educational institution. The success of educational institutions will be greatly influenced by the success of alumni in the process of getting a job or continuing their education. The more alumni who succeed in their work, the better the rating of the educational institution because many companies employ them or who successfully continue their education to the next level. Vocational High School is considered able to answer the problems of employment and unemployment. Vocational education is part of the education system that prepares a person to be better able to work in one occupational group or field of work than in other occupations. SMKs also assist with re-industrialization through three main groups: training young people for work, training current workers, and returning to the workforce. One of the successes of educational institutions can be determined by how successful graduates are when they are in the community. The ratio of graduates who have worked to those who have not worked, the average waiting period for work, the field of work occupied, the amount of income received when they first worked, and others. One method to obtain appropriate data is to use a tracer study, which is an academic activity to obtain feedback from graduates about the relevance of the educational process that has been undertaken with the ability to improve the quality of life of graduates in the community. Tracer study is a tool to obtain data needed for the development of an educational institution. The process of obtaining tracer study data can use a computer connected to the internet so that the process becomes easier because it can be accessed anytime and anywhere. The data obtained from the study tracer is processed according to the need for the data, one method that can be used is NaÃ¯ve Bayes. NaÃ¯ve Bayes algorithm is one of the methods used based on probabilistic reasoning.